2013
DOI: 10.1136/bcr-2013-009519
|View full text |Cite
|
Sign up to set email alerts
|

Orbital apex syndrome secondary to granulomatosis with polyangiitis

Abstract: Orbital apex syndrome (OAS) is an optic nerve dysfunction with palsy of the third, fourth and sixth cranial nerves and ophthalmic division of the fifth cranial nerve. Causes can be infective, inflammatory, traumatic, neoplastic or vasculitic. We describe the first case in British literature and second worldwide of OAS presenting as granulomatosis with polyangiitis (GPA). A 38-year-old patient presented with left periorbital swelling and pain. An examination revealed left eye proptosis, tenderness in the ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Steroid pulse therapy followed by oral medication of prednisolone and cyclophosphamide resulted in an improvement in diplopia, facial palsy, meningeal thickening, and orbital abnormalities. Siddiqui et al [ 8 ] also reported a case of GPA presenting with OAS who achieved good recovery. Laboratory data showed an elevation in inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroid pulse therapy followed by oral medication of prednisolone and cyclophosphamide resulted in an improvement in diplopia, facial palsy, meningeal thickening, and orbital abnormalities. Siddiqui et al [ 8 ] also reported a case of GPA presenting with OAS who achieved good recovery. Laboratory data showed an elevation in inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, orbital involvement is the most frequent manifestation, occurring in 22–45% of cases with ocular manifestations [ 3 , 4 , 5 ]. As a rare ocular manifestation, orbital apex syndrome (OAS) associated with GPA has been demonstrated in several reports [ 6 , 7 , 8 , 9 ]. OAS is characterized by optic neuropathy and total ophthalmoplegia caused by the damage of II, III, IV, V1, and VI cranial nerves due to the lesion of the orbital apex.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these cases, OAS was caused by contiguous sinus or pachymeningeal infiltration. [3][4][5][6][7][8] OAS without contiguous sinus spread has been reported, but occurred in a patient with a pre-existing confirmed diagnosis of GPA. 9 This case highlights several key points.…”
mentioning
confidence: 99%